Antibacterial Effect of Caesalpinia sappan L. Aqueous Decoction on Staphylococcus aureus - Sri Tumpuk; laila kamilla; Sutriswanto Sutriswanto; Alya Dwinanda Kusumastuti (poltekkes kemenkes pontianak, 2026)
Secang (Caesalpinia sappan L.) is a plant frequently utilized in herbal medicine due to its therapeutic properties. Sappan wood contains various bioactive compounds, such as flavonoids, saponins, and tannins, which can inhibit the growth of Staphylococcus aureus. Staphylococcus aureus is a bacterium responsible for conditions such as pressure sores, abscesses, impetigo, cellulitis, and staphylococcal scalded skin syndrome. The aim of this study was to determine the differences in antibacterial activity of sappan wood decoctions at concentrations of 70%, 80%, 90%, and 100% in inhibiting the growth of Staphylococcus aureus. This study employed a quasi-experimental method with a purposive sampling technique. The samples consisted of 70%, 80%, 90%, and 100% concentrations of sappan wood decoction, each repeated six times for a total of 24 samples. Antibacterial testing was conducted using the Kirby-Bauer diffusion method. The results showed that 100% of the tested sappan wood decoction concentrations successfully inhibited the growth of Staphylococcus aureus, with the average inhibition zones being 25 mm at a 70% concentration, 27.16 mm at 80%, 28.58 mm at 90%, and 30.58 mm at 100%. There was a significant relationship between the concentration of sappan wood decoction and its antibacterial activity (p = 0.000). Based on these results, even the lowest concentration of 70% is highly effective for inhibiting the growth of Staphylococcus aureus.